Propensity score matched analysis comparing the clinical outcome of Klebsiella pneumoniae and Escherichia coli causing community-onset monomicrobial bacteremia. Issue 26 (June 2017) - Kuo, Tsung-Hang; Yang, Chao-Yung; Lee, Chung-Hsun; Hsieh, Chih-Chia; Ko, Wen-Chien; Lee, Ching-Chi
Abstract : Abstract: Bacteremia is a life-threatening condition that is associated with substantial healthcare costs. Escherichia coli and Klebsiella pneumoniae are the leading causes of community-onset gram-negative bacteremia. However, a comprehensive comparison between these pathogens involved in bacteremia episodes has yet to be reported. In this retrospective cohort study, adults with community-onset monomicrobial bacteremia caused by E coli or K pneumoniae were recruited in the emergency department of a medical center during a 6-year period, and the clinical variables were collected retrospectively from medical records. The complicated abscess occurrence was determined through imaging studies, according to the opinion of an infectious disease consultant. According to the independent predictors of 28-day mortality identified through multivariate regression analyses, patients in the E coli group were propensity score matched (PSM) in a 1:1 ratio to those in the K pneumoniae group. A total of 274 and 823 adults with K pneumoniae and E coli bacteremia were included in the present study. The K pneumoniae group had more patients with fatal comorbidities (McCabe classification), critical illness (Pitt bacteremia score ≥ 4) at bacteremia onset, and initial syndrome (e.g., severe sepsis and septic shock) as well as a higher crude mortality rate than did the E coli group. After appropriate matching, no significant differences were observed in the critical illness at bacteremia onset, initial syndrome, major comorbidities, and comorbidity severity of the 2 groups ( E coli, n = 242; K pneumoniae, n = 242). Furthermore, despite similar 14- and 28-day crude mortality rates between the 2 PSM groups, more frequent abscess occurrences and a longer length of hospitalization were observed in the K pneumoniae group than in the E coli group. Conclusively, numerous clinical features at initial presentations varied between the E coli and K pneumoniae groups. Despite conducting a PSM analysis to control the differences in the baseline characteristics, a longer length of hospitalization and more frequent abscess occurrences were observed in the K pneumoniae group than in the E coli group.